Violet & Jobie in the wild - Perkins, Lynne Rae (Greenwillow Books, 2022)
Brother and sister mice Violet and Jobie live a cozy and comfortable life in a human house, and they are more than happy to stay inside forever. Violet especially loves watching nature shows with the young boy that lives in the house, but the boy's mother isn't a fan of mice and sets a trap for them when she learns of their existence. When Violet and Jobie are caught in the trap, the young boy pleads with his mother to release them, so she sets them loose outside. Violet and Jobie suddenly find themselves in the wild and must find a way to survive.